Pengaruh Keadilan Organisasi dan Kepuasan Kerja Terhadap Komitmen Organisasi Kepala SMA Negeri di Jakarta - Musringudin Musringudin; Yulian Dinihari (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2021)
ABSTRACT The objective of this research is to measure the effect degree of organizational justice and job satisfaction toward organizational commitment of the principals of public high school in Jakarta. The data were collected from the principals that selected as a respondent through the questionnaires and analyzed using path analysis. The result of the study shows: there is a positive effect of organizational justice variable on organizational commitment. The data analysis said the path coefficient value of organizational justice on organizational commitment described a positive contribution. The effect of job satisfaction on organizational commitment was also showed a positive correlation. The data of organizational justice variable was also indicated a positive influenced on the job satisfaction. Keywords: Organizational Justice, Job Satisfaction, Organizational Commitment